The Validity of Okun’s Law, Case of Jordan - Al-hosban, Saleh; Edienat, Mohmmad (European Scientific Journal, ESJ, 2017)
The main aim of this study is to empirically examine ,investigate and test the relationship between unemployment rate and economic growth within Jordanian economy over the period of time (1982-2016), in order to examine the validity of Okun’s law, which suggests a negative relationship between unemployment rate and economic growth, several economic methods are employed by using descriptive statistics, as well as some econometric tests, in order to analyze the variables under study . The empirical results of this study show a negative relationship between unemployment and GDP in the period 1982-2016 in Jordanian economy, which is consistent with Okun’s law. In other word, this study offered an additional empirical evidence to confirm the validity of the Okun’s law in the case of Jordan over the period 1982-2016.So any attempt to increase economic growth through some economic policies such as expansion in spending would reduce unemployment rate, where the Okun’s coefficient of GDP with respect to unemployment rate is- 0.004, such that an increase of 100 million Jordanian Dinars in the Real GDP will cause 40% decrease in the unemployment rate, which is about half percent in unemployment rate in the next. The findings of this thesis may help economists and policymakers when adapting policies in order to adjust unemployment level in the economy.